Nog-da-win-da-min: A Collaborative Consultation with First Nations about Children’s Well-being - Schmidt, Heather; Broad, Gayle; Sy, Christine; Johnston, Rosalind (First Peoples Child & Family Review, 2012)
The history of the relationship between child welfare agencies in Canada and First Nations has been fraught with pain, and the removal of children from their families and communities is often described as an attempted cultural genocide. The realities of colonization, residential schools, and the “60s scoop” have created a legacy of pain and distrust which can be difficult for today’s Native child welfare services to address. Nog-da-win-da-min Family and Community Services (NFCS) is an Anishinaabe agency that decided to consult with its seven member communities in order to obtain their input about future service development, but, with this legacy, were unsure how to engage the communities in meaningful dialogue. As such, they partnered with a team of researchers at NORDIK Institute to design and carry out a communitybased consultation. This article explores the collaborative process of creating and tailoring a consultation method to be an empowering and positive experience for participants, to be conducted within safe and accessible spaces throughout the communities. This required a thoughtful process development, which respected participants’ knowledge and experiences (local knowledge), accommodated intergenerational trauma with sensitivity, and that employed Indigenous language and concepts (such as the Medicine Wheel) to guide the process. This article outlines some key learnings for others undertaking similar dialogues and consultations.